AC and DC field distributions in glass, RTV-coated glass and composite insulators - Uckol, Halil Ibrahim; Ilhan, Suat; Ozdemir, Aydogan (IEEE, 2019)
This study presents numerical electric field distribution of conventional glass, RTV (Room Temperature Vulcanizing) silicone rubber coated glass and silicone rubber insulator strings used for 154 kV transmission systems. 2D axisymmetric electric field simulations were performed by using a commercially available software based on Finite Element Method. Simulation studies include both AC and DC excitations. The volume conductivity effect of the air surrounding the insulators was taken into account. Electric field and voltage distribution along creepage distance of these three types of insulators were investigated. The results were evaluated in terms of types of insulators, types of voltages and their effects on the field distribution.